Acid resistance of metakaolin-based, bamboo fiber geopolymer composites - Ribeiro, Marilene Gomes de Sá; Sá Ribeiro, Marilia G.; Keane, Patrick F.; Sardela, Mauro R.; Kriven, Waltraud M.; Sá Ribeiro, Ruy A. (Construction and Building Materials, 2021)
This study focuses on calcined kaolin, commercial sodium silicate, and Amazonian bamboo to make geopolymer. The durability of geopolymer matrix (GP) and bamboo fiber geopolymer composite (GPBF) materials was analyzed by studying the resistance to the exposure to sulfuric and hydrochloric acids at concentrations from 0 to 15 wt%, testing two different geometry of samples. The microstructure of the raw and composite materials was investigated by X-ray fluorescence and scanning electron microscopy. Geopolymer formation was confirmed by X-ray diffraction with a characteristic amorphous hump at 28° two theta and a few crystalline peaks of quartz. Visual appearance, mass change, and compressive strength behavior of all GP and GPBF samples immersed in 0, 5, 15 wt% of H2SO4 and HCl for 7, 28, and 112 days were investigated. GP and GPBF did not change in appearance, and no mass loss was observed in 0% acid (100% water) solution pH 12, an alkali solution due to partial dissolution of NaOH from the GP matrix, denoting durability in water. GP mass loss increased with varying sulfuric acid concentrations from 5, 10, and 15 wt%, resulting in values of 2.7%, 3.5%, and 4.4%, respectively. In general, the GP and GPBF specimens experienced higher compressive strength degradation when exposed to H2SO4 than to HCl. GP and GPBF can safely be applied as construction materials in applications exposed up to 15 wt% sulfuric or hydrochloric acid environments, including in sewage systems. © 2021 Elsevier Ltd
Keywords: Compressive strength; Durability; Hydrochloric acid; Sodium waterglass; Sulfuric acid; Sustainable composites